Diet therapy for infectious diseases in children - A. A. Ploskireva (Лечащий Врач)
The change in metabolism in infectious diseases in children is characterized by the same type of metabolic changes and is due to a combination of a significant increase in the body's need for energy and protein-energy substrates with tissue tolerance for their assimilation. At the same time, the severity of the course of the infection determines the development of relative nutritional deficiency. Metabolic disorders that develop in infectious diseases in children are in the nature of a stereotypical stress reaction, characterized by the development of an imbalance in the metabolism of carbohydrates, proteins and fats against the background of an increase in the body's needs for protein-energy substrates. The article deals with the problem of the importance of a balanced diet in children with infectious diseases. It is shown that the main approaches to diet therapy should be stages, taking into account the child's age and the severity of the disease. One of the significant aspects of preventing the negative impact of the infectious process and, for example, antibacterial therapy is the appointment of functional food products containing probiotic components.